The sports doping market: understanding supply and demand, and the challenges of their control - Paoli, Letizia (Springer, 2014)
This book examines sports doping from production and distribution, detection and punishment. Detailing the daily operations of the trade and its gray area as a semi-legal market, the authors cover important issues ranging from athletes most at risk to the role of organized crime in sports doping, and whether sports governing bodies are enabling the trade. Challenges for law enforcement and legislation, and efforts to control PED use in the worldwide sports community and among aspiring athletes, are also discussed in depth. The book's extensive research: Estimates the demand for performance-enhancing products. Traces the route from legal substances to illegal uses. Identifies classes of suppliers and their methods of operation. Tracks typical distribution systems from suppliers to users. Examines the economics of the market: prices, profits, revenue. Assesses the state of anti-doping law enforcement efforts.Starting with an unprecedented case study in Italy, the intense scrutiny from one pivotal country yields a potential template for research and policy on a world scale. Doping and Sport makes solid contributions to the work of researchers in criminology and criminal justice, particularly with an interest in corruption, drug trafficking, and criminal networks; researchers in sports science and public health; and policymakers.--